GEOCAPABILITIES COMPETENCE OF HIGH SCHOOL GEOGRAPHY TEACHERS IN CENTRAL JAVA, INDONESIA; WHAT IS IT AND HOW DO WE ASSESS IT? - Dannis Ni'matussyahara; Sugiyanto Sugiyanto; Sarwono Sarwono (Universitas Sebelas Maret (UNS), 2025)
GeoCapabilities aims to encourage the proposition of geography as a strong disciplinary knowledge and the role of teachers as the key in bringing knowledge to learners. This study aimed to determine the level of understanding of GeoCapabilities of geography teachers in high schools in Karanganyar Regency. The method used was descriptive qualitative, with 28 respondents. The type of research is qualitative with a descriptive approach. Data collection techniques include questionnaires, test questions, interviews, and documentation. Data analysis techniques using Interactive Model and Percentage. GeoCapabilities knowledge test results on each indicator obtained; 1. Geography imagination (26.16%), 2. Empathy (22.5%), 3. Integrative thinking (23.6%), 4. Spatial thinking (20.5%), 5. Exploration (29.25%). Based on the GeoCapabilities test results, the average score obtained by geography teachers is 3.6, with a maximum score achievement percentage of 46.6%. If the knowledge test score is in the range > 36% - 52%, it is included in the